Aplikasi Metode Kaplan Meier sebagai Penduga Ketahanan Hidup Penderita Kanker Payudara (Jurnal EurekaMatika, 2021)
Survival analysis is a statistical method for analyzing an event for one or more populations. Basically, for analyzing the survival rate, uncensored data of the object is needed. Uncensored data is a data that we got from an individu (research object) and every developments of the object start from the beginning until the end of the research is written well. In the fact, uncensored data is hard to find in a real life because of many factors. For example, the individu is fully recovered before the research ended, or the individu did not want to be research object anymore. Because of that, we need a method for estimating the survival function that using the censored data. This article will discuss the determination of the probability of survival of the censored data using the Kaplan Meier method. The survival function obtained by the Kaplan Meier method is called the Kaplan Meier curve. The curve illustrates the probability of survival of individuals who are the object of research. In addition, an application program is designed to calculate the life time and the probability of survival using an Excel Visual Basic For Application (VBA) computer program. The program not only can be used for writing the data about cancer, but also for obtain an information about the survival probability so it can be more efficient for the researcher. In general, survival analysis using Kaplan Meier method resulted in the conclusion that the life time of breast cancer patients who undergo chemotherapy treatment has a greater chance of life than breast cancer patients who do not undergo chemotherapy treatment.ABSTRAKSurvival analysis atau analisis ketahanan hidup merupakan teknik statistika untuk menganalisis data waktu hidup pada kejadian atau event pada satu atau lebih populasi. Pada dasarnya untuk menganalisis suatu ketahanan hidup dibutuhkan data lengkap (data tak tersensor) dari objek yang diteliti. Pada kenyataannya data tak tersensor jarang sekali dijumpai dikarenakan oleh beberapa faktor diantaranya individu yang telah sembuh sebelum penelitian berakhir atau individu menolak untuk melanjutkan diri sebagai objek penelitian. Oleh karena itu, dibutuhkan suatu metode untuk menduga fungsi ketahanan hidup yang melibatkan data tersensor. Artikel ini akan membahas mengenai penentuan probabilitas fungsi ketahanan hidup data tersensor dengan menggunakan metode Kaplan Meier. Fungsi ketahanan hidup yang diperoleh dengan metode Kaplan Meier dinamakan kurva Kaplan Meier. Kurva tersebut menggambarkan probabilitas ketahanan hidup individu yang menjadi objek penelitian. Selain itu, dilakukan perancangan program aplikasi perhitungan waktu hidup serta probabilitas ketahanan hidup dengan menggunakan program komputer Excel Visual Basic for Application (VBA). Program ini dapat digunakan sebagai alat bantu pendataan penderita kanker payudara serta mengetahui probabilitas ketahanan hidupnya sehingga akan mengefisienkan waktu dan tenaga yang diperlukan. Secara umum, analisis ketahanan hidup menggunakan metode Kaplan Meier menghasilkan kesimpulan bahwa waktu hidup penderita kanker payudara yang menjalani pengobatan kemoterapi memiliki peluang hidup yang lebih besar dibandingkan penderita kanker payudara yang tidak menjalani pengobatan kemoterapi.
Keywords: Analisis Survival; Data Tersensor; Excel Visual Basic for Application; Metode Kaplan Meier